A case of late death after treatment for medulloblastoma - Balažic, Jože; Vogrin, Andrej; Jereb, Berta (Onkologija : Slovenian Journal of Oncology, 2010)
A 27-year-old male was treated for medulloblastoma with complete removal of tumor, postoperative RT to CNA with 36 Gy and boost to the posterior fossa 16 Gy. Nine years later, a suprasellar recurrence was treated with Carboplatin and Vepezid and 33 Gy to the tumor bed. Three years later he complained about headaches, periodic loss of conciousness and progressively showed bizarre behavior. He was referred to psychiatrist. No recurrence was found. He did not appear on the day of follow-up appointment. He died at home, at the age of 43 years, 16 years after the first treatment. The cause of death determined by forensic autopsy : anemic subacute infarction in the left cerebellum.